The Shape and Orientation o f the Domain Units in the "Round Tablets" of Ur III Girsu - Maekawa, K.
A Critical Review of Liverani, M., The Shape of Neo-Sumerian Fields, BSAg 5 (1990) 147-186, esp. 155ff.